Outcome of image-guided biopsies: Retrospective review of the West of Scotland musculoskeletal oncology service. Issue 2 (April 2016) - Ferguson, Kim B.; McGlynn, Jennifer; Jane, Michael; Ritchie, David; Mahendra, Ashish
Abstract: Introduction: Image-guided needle biopsy of a suspected musculoskeletal malignancy has become increasingly popular as an effective modality for diagnosis. Our aim was to determine accuracy and success rates of the image guided biopsies performed by our service. Methods: A retrospective review of the Bone and Soft Tissue Sarcoma service database was performed to identify all patients who underwent image guided biopsy and to identify the results of such investigations. Patients who had an open biopsy or a biopsy performed at another institution were excluded from this review. A biopsy was deemed successful if a sample of the target lesion was sampled at the time of biopsy. The successful biopsies were then classified as diagnostic or non-diagnostic depending on whether the diagnosis was established from the sampled tissue. Results: 465 of the 1181 new referrals to the Bone and Soft Tissue Sarcoma service in a 4 year period underwent biopsy. 75% (350) were image guided biopsies – 60% (281) ultrasound and 15% (69) CT guided. The rate of successful ultrasound guided biopsy was 94.7% and the rate of a successful diagnostic biopsy was 93.6%. CT guided biopsies were successful in 95.7% and were both successful and diagnostic in 79.7%. Discussion: The rate of a successful diagnostic ultrasound biopsy within our institution reflects the reported rate within the literature. The rate of a successful diagnostic CT guided biopsy is lower however is also consistent with that reported within the literature. Low grade lipomatous lesions and chondroid lesions of undetermined malignant potential (CLUMP) are associated with a more difficult histological diagnosis on biopsy alone which is consistent with our findings. For this reason our institution has stopped performing routine image guided biopsies on these lesions. Radiological low grade lipomatous lesions are treated with marginal excision and all CLUMP lesions undergo open biopsy.